2002
DOI: 10.1183/09031936.02.00257202
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon disease in lung transplant recipients: association with ciprofloxacin

Abstract: Achilles tendon disease in lung transplant recipients: association with ciprofloxacin. P.N. Chhajed, M.L. Plit, P.M. Hopkins, M.A. Malouf, A.R. Glanville. #ERS Journals Ltd 2002. ABSTRACT: Achilles tendonitis or rupture are uncommon complications following the use of fluoroquinolones, with a reported incidence in the general population of 0.4%. The aims of the current study were to determine the incidence of Achilles tendon disease (ATD) in lung transplant recipients (LTR) and to identify risk factors.Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 13 publications
(16 reference statements)
0
26
1
6
Order By: Relevance
“…This is in contrast to clinical observations and to our results but might be explained by the short treatment period of only 24 h. In a typical clinical situation, A c c e p t e d M a n u s c r i p t 16 patients are treated chronically with glucocorticoids for indications such as pulmonary diseases or following organ transplantation [14,50].…”
Section: Page 14 Of 37contrasting
confidence: 54%
“…This is in contrast to clinical observations and to our results but might be explained by the short treatment period of only 24 h. In a typical clinical situation, A c c e p t e d M a n u s c r i p t 16 patients are treated chronically with glucocorticoids for indications such as pulmonary diseases or following organ transplantation [14,50].…”
Section: Page 14 Of 37contrasting
confidence: 54%
“…Similarly, the fact that the 13:1 (M:F) gender ratio in our AT patients was not statistically significant is probably attributable to the small proportion of women in our sample; other studies have also found AT to be more frequent among men. 3,10,14 Little is known of the pathophysiologic mechanisms leading to quinolone-induced tendinopathy. Jorgensen et al 15 and Beuchar et al 16 suggested that an ischemic vascular process leading to tissue necrosis may cause the disorder, and LeHuec et al 17 indicated that it may be due to direct toxic insult to tendon collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Tendinitis was diagnosed if the tendon was painful upon walking and palpation and showed signs of local inflammation 5 during the first 30 days after the first quinolone dose. 10 Tendon rupture was diagnosed if Thompson's test 9 was positive. In unclear cases, an ultrasound study was performed.…”
Section: Diagnosis Of Tendinopathy and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsere Patientin wies eine Kombination aller genannten Risikofaktoren auf. Auch bei Patienten mit Zustand nach Nieren- [2] und Lungentransplantation [1] wurde über das Auftreten einer Tendopathie berichtet. Ob aber die Transplantation ein eigenständiger Risikofaktor für die Tendopathie ist, erscheint eher unwahrscheinlich.…”
Section: Diskussionunclassified